Effect of cold vapor for sore throat reduction in elderly patients with cardiac surgery: A randomized control trial - Maryam Sadat Nasorollahi; Nahid Rejeh; Mohammad Ziya Totonchi Ghorbani; Tahereh Bahrami; Majideh Heravi Karimooi (Journal of Nursing Advances in Clinical Sciences)
Cold vapor has anti-inflammatory properties and can relieve endotracheal complications like sore throats. As elderlies are more prone to post-extubation sore throat, this study investigates the effect of cold vapor on post-extubation sore throat in the elderly undergoing coronary artery bypass surgery. A randomized controlled trial was carried out on eighty elderly patients undergoing elective coronary artery bypass surgery at a cardiovascular therapeutic center in Iran. Participants were randomly assigned to each experimental and control group using the block randomization method (n=40 in each group). The experimental group received cold vapor after endotracheal tube extubation, and the control group received no treatment. Data were gathered at different time intervals 6, 12, 18, and 24 hours after post-extubation using the verbal rating score. Descriptive and inferential statistics were used to answer the research questions of this study. The results showed that the sore throats significantly differed between the two study groups over the four data collection points (P<0.05). Although the number of sore throats decreased in the control group, they were 0.51 times more likely to develop sore throats (Exp (B)=0.51). Cold vapor is a safe and easy strategy used by nurses for alleviating post-extubation sore throat in elderly patients after coronary artery bypass surgery. Combined with other therapeutic measures, cold vapor can be more effective and reduce the chance of developing sore throats in these patients.